2005
DOI: 10.1002/qua.20424
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale quantum effects in biological systems

Abstract: Particular aspects of large-scale quantum effects in biological systems, such as biopolymers and also microtubules in the cytoskeleton of neurons which can have relevance in brain functioning, are discussed. The microscopic (quantum mechanical) and macroscopic (quantum statistical mechanical) aspects, and the emergence of complex behavior, are described. This phenomena consists of the largescale coherent process of Frö hlich-Bose-Einstein condensation in open and sufficiently far-from-equilibrium biopolymers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Indeed, the calculated heating can be extreme (12), with some values exceeding T S /T ϭ 100 (i.e., T S Ͼ 30,000 K for a room temperature bath). Temperatures of this order serve primarily to indicate shortcomings in possible applications of the model.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, the calculated heating can be extreme (12), with some values exceeding T S /T ϭ 100 (i.e., T S Ͼ 30,000 K for a room temperature bath). Temperatures of this order serve primarily to indicate shortcomings in possible applications of the model.…”
Section: Resultsmentioning
confidence: 99%
“…S13, for condensates in the low temperature limit, these fluctuations become extremely large, and the time required to form the condensate increases to become of the microsecond time scale. The simulations of the condensate proposed by Mesquita et al (12,13) in protein amide-I vibrations at 300 cm Ϫ1 (10 THz) showed extremely large 400 kHz fluctuations in the strongly formed condensate.…”
Section: Coherent Motion Within Strong Frö Hlich Condensatesmentioning
confidence: 90%
See 3 more Smart Citations